An interpenetrating and patternable conducting polymer hydrogel for electrically stimulated release of glutamate. (1st January 2022) - Bansal, Mahima; Raos, Brad; Aqrawe, Zaid; Wu, Zimei; Svirskis, Darren
Abstract: Recent advances in drug delivery have made it possible to release bioactive agents from neural implants specifically to local tissues. Conducting polymer coatings have been explored as a delivery platform in bioelectronics, however, their utility is restricted by their limited loading capacity and stability. This study presents the fabrication of a stable conducting polymer hydrogel (CPH), comprising the hydrogel gelatin methacrylate (GelMA), and conducting polymer polypyrrole (PPy) for the electrically controlled delivery of glutamate (Glu). The hybrid GelMA/PPy/Glu can be photolithographically patterned and covalently bonded to an electrode. Fourier-transform infrared (FTIR) analysis confirmed the interpenetrating nature of PPy through the GelMA hydrogels. Electrochemical polymerisation of PPy/Glu through the GelMA hydrogels resulted in a significant increase in the charge storage capacity as determined by cyclic voltammetry (CV). Long-term electrochemical and mechanical stability was demonstrated over 1000 CV cycles and extracts of the materials were cytocompatible with SH-SY5Y neuroblastoma cell lines. Release of Glu from the CPH was responsive to electrical stimulation with almost five times the amount of Glu released upon constant reduction (-0.6 V) compared to when no stimulus was applied. Notably, GelMA/PPy/Glu was able to deliver almost 14 times higher amounts of Glu compared to conventional PPy/Glu films. The described CPH coatings are well suited in implantable drug delivery applications and compared to conducting polymer films can deliver higher quantities of drug in response to mild electrical stimulus. Statement of significance: Conducting polymer hydrogels (CPH) have been explored for the electrically controlled release of bioactives from implantable devices. Typically, the conducting polymer component does not fully penetrate the hydrogel. We report, for the first time, a completely interpenetrating CPH allowing for the full benefits of the composite material to be realised, the hydrogels provide a reservoir for drug delivery, and conducting polymer renders the material responsive to electrical stimulation for drug release. We report a CPH for the electrically controlled delivery of glutamate (excitatory neurotransmitter) where several-fold more glutamate can be delivered compared to conducting polymer films. The described CPH coatings are well suited for use in bioelectronic devices to deliver large quantities of drug in response to mild electrical stimulus. Graphical abstract: Image, graphical abstract